Astragalus mongholicus Bunge and Panax notoginseng formula (A&P) improves renal mesangial cell damage in diabetic nephropathy by inhibiting the inflammatory response of infiltrated macrophages - Xiao Lin; Xiao-qin Lei; Jie-ke Yang; Jian Jia; Xia Zhong; Rui-zhi Tan; Li Wang (BMC, 2022)
Abstract Background Diabetic nephropathy (DN) is one of the main causes of end-stage renal disease with scantly effective treatment. Numerous evidences indicated that macrophages play an important role in the occurrence and pathogenesis of DN by secreting inflammatory cytokines. Mincle is mainly expressed in macrophages and promotes kidney inflammation and damage of acute kidney injury. However, the role of Mincle in DN is unclear. In this study, we aim to investigate the effect of Mincle-related macrophage inflammation on DN, and whether it can be identified as the therapeutic target for Astragalus mongholicus Bunge and Panax notoginseng Formula (A&P), a widely used Chinese herbal decoction for DN treatment. Methods In vivo experiments high-fat and high-sugar diet and streptozotocin was used to establish a diabetic nephropathy model, while in vitro experiments inflammation model was induced by high-glucose in mouse Bone Marrow-Derived Macrophages (BMDM) cells and mouse mesangial (MES) cells. Kidney pathological staining is used to detect kidney tissue damage and inflammation, Western blotting, Real-time PCR and ELISA are performed to detect Mincle signaling pathway related proteins and inflammatory cytokines. Results Mincle was mainly expressed in infiltrated macrophage of DN kidney, and was significant decreased after A&P administration. The in vitro experiments also proved that A&P effectively down-regulated the expression of Mincle in macrophage stimulated by high glucose. Meanwhile, the data demonstrated that A&P can reduce the activation of NFκB, and the expression and secretion of inflammatory cytokines in DN kidney or BMDM cells. Notably, we set up a co-culture system to conform that BMDM cells can aggravate the inflammatory response of mesangial (MES) cells under high glucose stimulation. Furthermore, we found that the anti-injury role of A&P in MES cells was dependent on inhibition of the Mincle in macrophage. Conclusion In summary, our study found that A&P is effective in reducing renal pathological damage and improving renal function and inflammation in diabetic nephropathy by a mechanism mainly related to the inhibition of the Mincle/Card9/NFκB signaling pathway.